Analisis Efektifitas Komunikasi Pemasaran Untuk Produk Le Minerale Melalui Media Televisi Terhadap Minat Beli: isi pesan, struktur pesan, format pesan, sumber pesan, media televisi, minat beli - Sudaryana, Arif; Imam Basri, Anindita; Pratiwisari, Dyah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This research aims to determine the influence of message content, message structure, message format, message source, and television media on purchasing interest in bottled drinking water products under the Le Minerale brand in the Special Region of Yogyakarta. The method used in this research is a quantitative method. The data in the research is primary data with data collection techniques using questionnaires. Sampling used purposive sampling technique. Data analysis used SPSS version 26.0, the analysis technique used multiple linear regression analysis with a significance level of 0.05. The results of this research show that the variables of message content, message structure, message format, message source, and television media have a positive and significant effect on purchase interest in bottled drinking water products under the Le Minerale brand. This research is limited to message content, message structure, message format, message source, and television media on purchasing interest.